Evolución de la exportación de muebles en madera para el hogar desde el departamento del atlántico hacia panamá periodo 2009 – 2012 y perspectivas para el 2013 (2013)
This research covers the bilateral trade between the department of Atlántico and the Panama apartment market of wooden furniture for the home in the 2009-2012 time period. It contains the importance of the Panama market by their economic indicators and the history of this trade, and details of its evolution each of the years. We describe the major companies of the two countries, as well as the Panama market, by means of market research, to know the taste and trends of the target population. It also includes the outlook for this year, conclusions and recommendations.